Industrial Clusters and Corporate Social Responsibility in Developing Countries: What We Know, What We do not Know, and What We Need to Know - Lund-Thomsen, Peter (Journal of business ethics, 2016)
This article provides a review of what we know, what we do not know, and what we need to know about the relationship between industrial clusters and corporate social responsibility (CSR) in developing countries. In addition to the drivers of and barriers to the adoption of CSR initiatives, this study highlights key lessons learned from empirical studies of CSR initiatives that aimed to improve environmental management and work conditions and reduce poverty in local industrial districts. Academic work in this area remains embryonic, lacking in empirical evidence about the effects of CSR interventions on the profitability on local enterprises, workers, and the environment. Nor do theoretical frameworks offer clear explanations of the institutionalization and effects of CSR in local industrial districts in the developing world. Other key limitations in this research stream include an excessive focus on export-oriented industrial clusters, the risk that CSR becomes a form of economic and cultural imperialism, and the potential for joint-action CSR initiatives in clusters of small and medium-sized enterprises to offer a new form of greenwashing. From this review, the authors develop a theoretical model to explain why CSR has not become institutionalized in many developing country clusters, which in turn suggests that the vast majority of industrial clusters in developing countries are likely to engage in socially irresponsible behavior.